A relevância da infraestrutura física da escola segundo os servidores do Colégio Estadual Nazaré Nunes da Silva - SILVA, CAMILO MACHADO DA (Universidade Federal do Tocantins, 2022)
This article has as goal to analyze the importance that the public servers from the Girassol de Tempo Integral Nazaré Nunes da Silva High School (Full-time School) have attached to the physical infrastructure. The Full-time High School was contemplated to reform and enlargement by the Estrada do Conhecimento Program, Tocantins State Program in partnership with the World Bank. The methodological ways to get to the result of this article formed the following steps: a) bibliographic review to understand the concept of State and its relation with the education, to comprehend the questions related to physical structure of the school spaces and to understand what Estrada do Conhecimento Program was; b) Application of questionnaires to public servers and ex-servers from the High School, suchlike to obtain quantitative and qualitative data about the meaning of school and its infrastructure on the servers’ conception; c) Analyses of the data obtained from the research, by considering the evaluations which the servers make analysis about the new structure. The research result has pointed out that after the school reform the teaching learning process got better, however some problems persist, such as lack of conditioned air sets in the classroom and the others. Although, the study case reveals that the infrastructure, highlighted for its landscaping, for the sport/recreation and security spaces are extremely important to construct the school as the belonging place.